The Considerations of Eugeniusz Kwiatkowski on the Role of Collective Social Work in the Process of Liquidating the Economic and Social Disparities of the II Republic of Poland - Lityńska, Aleksandra (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The aim of the article is to analyse the socio-economic programme of Eugeniusz Kwiatkowski in the II Republic of Poland, based on the idea of collective social work. Kwiatkowski posited solidarity and the creative efforts of all citizens as a basis for strengthening the economic and political position of the country in the international arena. Fulfilling the duties of the Minister of Industry and Trade and then deputy Prime Minister and Minister of the Treasury, he contributed to the development of strategic sectors of the economy, mainly in the COP (Central Industrial Region), Gdynia, Stalowa Wola, and Mościce.